Anthropometrical parameters and body composition influence swimming performance in young swimmers - Lätt, E.; Jürimäe, J.; Haljaste, K.; Cicchella, A.; Purge, P.; Jürimäe, T. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Participating in a competitive sport at a young age has been associated with specific body proportions (Damsgaard et al., 2001). The present study analysed the development of the anthropometrical parameters and body composition in young swimmers and assessed the effect of these parameters on swimming performance during biological maturation. Methods: Main anthropometrical parameters and biological age were measured in 55 young swimmers (29 males and 26 females). Maximal 400-m front-crawl swimming test was performed in a 25-m swimming pool, where the energy cost of swimming (Cs) was assessed. Peak oxygen consumption (VO2peak) was assessed by means of the backward-extrapolation technique recording VO2 during the first 20 sec of the recovery period after a maximal trial of 400-m distance. Body composition parameters were measured using dualenergy X-ray absorptiometry (DXA). ' Results: During the 2-year follow-up study period, the age, height, body mass, fat free mass (FFM), bone mineral mass (BM), arm span, and biological maturation values for all swimmers, body mass index (BMI) and spine BMD for boys and body fat% and total BMD for girls significantly increased during each year (p<0.05). Partial correlation analysis revealed that 400-m swimming performance time was elated (p<0.05) to body height (r>-0.468) and arm span (r>-0.397) values, VO2 was related to body height (r>0.395) and arm span (r>0.394) at all three measurements after controlling for age and pubertal status in boys. In addition, the Cs of the 400-metre swimming performance was related (p<0.05) to the body mass (r>0.411), BMI (r>0.412), and spine BMD (r>0.500) values at all three measurement points in girls. Tracking of the measured physical characteristics over the two year study period was very high for boys (r>0.880) and relatively high for girls (r>0.694). Discussion: Swimmers usually start serious training at a very early age, and anthropometrical parameters affect swimming performance in young swimmers (Jürimäe et al., 2007).The result of present study also found that swimmers with good anthropometrical characteristics also have a better swimming time. The tracking coefficients of the physical parameters were high; hence it is important to pay attention to the selection process of young female swimmers. Anthropometric parameters track highly during puberty (Leppik et al., 2006) and the early biological maturation of swimmers has been attributed to sport-specific selection (Baxter-Jones et al., 1995).